Cost Analysis and Feasibility Study for Off-Grid Solar Power Plants (PLTS) in Pinggir Laut Village, Rokan Hilir Regency - Elvy Sahnur Nasution; Rahmat Fauzi Siregar; Faisal Irsan Pasaribu (JET (Journal of Electrical Technology), 2026)
Power facilities that use solar radiation to generate electricity are known as solar power plants. As an alternative energy source, using the sun for energy demands has a lot of promise in today's world. The energy generated or released by a light source is the sun. As is well known, the sun provides a significant portion of the world's illumination energy. In this situation, solar energy may be used in conjunction with other machinery that contributes and has the ability to convert solar radiation into electrical energy through the use of solar panels, which are apparatuses that transform solar radiation into electrical energy. Apart from that, solar panels are the most promising and have the most potential when compared to other energy sources. It can be argued that solar panels are the primary factor in optimising the potential of solar energy reaching the earth. The weather affects solar panel performance. Solar panels must constantly be pointed in the direction of the sun's rays in order to work well, as the sun's location on the surface of the planet varies with time. From the explanation above, a plan was made for a solar power plant in Pinggir Laut Village, Rokan Hilir Regency complex using 60 units of 200 WP panels, 56 units of 12V 100 Ah batteries, 2 units of 8000W inverter, and 2 units of a charger controller with a voltage rating of 120 Ampere. Keywords: Feasibility, PLTS, Planning, Photovoltaic, Power plants.